Innocents on the ice : a memoir of Antarctic exploration, 1957 - Behrendt, John C., 1932- (University Press of Colorado, 1998)
Innocents on the Ice is based on the author's experience and writings as part of a U.S. Navy-supported scientific expedition to establish Ellsworth Station on the Filchner Ice Shelf. This expedition, undertaken from November 1956 to early 1958, coincided with the International Geophysical Year (1957-1958) which ushered in the "scientific age" in Antarctica.